The Constructivist Turn in Political Representation and its Challenges to Democratic Legitimacy: Lessons from Participatory Institutions in Brazil. Issue 3 (3rd July 2019) - Almeida, Debora Rezende
ABSTRACT: The goal of the article is to review Saward's constructivist model by examining his broad view of legitimacy from the perspective of a particular experience, namely, the Participatory Institutions in Brazil. Participatory institutions highlight two flaws in Saward's account of legitimacy based on acceptance: the differences in the process of legitimation depending on where social actors present their claims and the paradox between control and decisiveness. First, civil society representatives operate inside the state structures, navigate in multiple spaces and have to interact with a diversity of actors: the affected public, other non-electoral representatives, and governmental actors. The legitimation process in participatory institutions depends profoundly on the interconnections among actors and spaces, which have the potential to obfuscate conditions of acceptance. I propose to adopt an interactive criteria of legitimacy based on systemic engagement of the represented. Second, participatory institutions highlight the paradox between constituencies' control and the representativés need to be decisive, demonstrating the limits of the constituencies' provisional acceptability throughout time. I argue that it is important to consider the trade-offs between control and decisiveness, asking how the influence of representatives on policy decisions conflicts with their need to nurture a continuous relationship with the constituency.